Barriers to Implementation of Climate Adaptation Frameworks by State Departments of Transportation. Issue 1 (January 2015) - Dowds, Jonathan; Aultman-Hall, Lisa
Disruptive events caused by weather extremes are imposing significant and rising costs on transportation agencies. In response, federal and state transportation agencies and other organizations are exploring adaptation measures to reduce the adverse consequences of these events. Several existing adaptation frameworks are synthesized here into a simplified, core adaptation framework, and the study seeks to delineate the current barriers to the widespread implementation of adaptation programs by state departments of transportation in the United States. From interviews with transportation practitioners and a review of the results from FHWA pilot projects, it is found that uncertainty about future climate conditions, the need for additional vulnerability-modeling tools, conceptual uncertainty about evaluating asset criticality, and limited funding all inhibit implementation of adaptation measures.